Unraveling the dynamics of emotional regulation and parental warmth across early childhood: prediction of later behavioral problems - Aimé Isdahl-Troye; Paula Villar; María Álvarez-Voces; Estrella Romero (Scientific Reports)
Abstract The impact of behavioral problems on children’s psychosocial health underscores the importance of identifying early predictors. Research in developmental psychopathology highlights emotion regulation (ER) and parenting as critical processes for fostering childhood adjustment, though their transactional dynamics remain underexplored. This study examines the bidirectional relationship between child ER and parental warmth during early childhood and investigates how their interconnected development predicts behavioral problems by school age. The sample, drawn from the longitudinal ELISA project, comprised 2,341 children (48.2% girls; ages 3–10). A Random Intercept Cross-Lagged Panel Model (RI-CLPM) was employed to distinguish individual-level differences from within-person changes, providing a more nuanced perspective. Results indicated stable individual differences in ER and parental warmth over time, even accounting for sociodemographic and temperamental factors. At the within-person level, bidirectional relations emerged: children’s emotional competencies influenced parental warmth, while parental warmth fostered children’s emotional skills. These reciprocal cycles predicted later behavioral outcomes. Specifically, carry-over changes in ER significantly predicted both conduct and emotional problems, whereas carry-over changes in parental warmth predicted only emotional problems. Findings are discussed in terms of the relevance of the interplay between ER and warmth in preventing internalizing and externalizing behaviors during childhood.